2011
DOI: 10.1007/s00281-011-0280-x
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between coagulation and complement—their role in inflammation

Abstract: The parallel expression of activation products of the coagulation, fibrinolysis, and complement systems has long been observed in both clinical and experimental settings. Several interconnections between the individual components of these cascades have also been described, and the list of shared regulators is expanding. The coexistence and interplay of hemostatic and inflammatory mediators in the same microenvironment typically ensures a successful host immune defense in compromised barrier settings. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
327
1
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(347 citation statements)
references
References 164 publications
(207 reference statements)
9
327
1
10
Order By: Relevance
“…Both the complement and the coagulation cascade originate from the same ancestral pathways, they comprise several serine proteases with common structural characteristics, and they show a high degree of interaction between specific intermediates (Amara et al, 2010;Krem and Di Cera, 2002). As both systems serve as defense mechanism in an environment with compromised barrier setting, they often activate each other (Oikonomopoulou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Both the complement and the coagulation cascade originate from the same ancestral pathways, they comprise several serine proteases with common structural characteristics, and they show a high degree of interaction between specific intermediates (Amara et al, 2010;Krem and Di Cera, 2002). As both systems serve as defense mechanism in an environment with compromised barrier setting, they often activate each other (Oikonomopoulou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Besides lysis of bacteria, C5b-9 can damage the cells and tissues of the host. It can induce tissue factor activity on endothelial cells (8), and prothrombinase formation on platelets (9, 10) and endothelial cells (11), thus contributing to development of multiple organ failure (12). Activation of complement, inflammation, and coagulation together promote thrombocytopenia and disseminated intravascular coagulation (DIC), a potential lethal thrombo-hemorrhagic complication of sepsis (13).…”
mentioning
confidence: 99%
“…British Journal of Haematology, 146,[538][539][540][541][542][543][544][545] Hanaoka, N., Murakami, Y., Nagata, M., Nagakura, S., Yonemura, Y., Sonoki, T., Kinoshita, T. & Nakakuma, H. (2012) Complement C3 is a substrate for activated factor XIII that is cross-linked to fibrin during clot formation Complement C3 is the main effector protein of the complement system and plays a major role in innate immunity. A growing body of evidence indicates complex interactions between the complement and coagulation cascades (Oikonomopoulou et al, 2012), which are likely to be beneficial in the context of protection following injury. We previously identified C3 as a novel clot component and demonstrated that C3 binds to fibrin with high affinity and prolongs fibrinolysis in a purified system and plasma milieu (Howes et al, 2012), consistent with results of several clinical studies (Schroeder et al, 2010;Hess et al, 2012;Howes et al, 2012).…”
mentioning
confidence: 99%
“…A growing body of evidence indicates complex interactions between the complement and coagulation cascades (Oikonomopoulou et al, 2012), which are likely to be beneficial in the context of protection following injury. We previously identified C3 as a novel clot component and demonstrated that C3 binds to fibrin with high affinity and prolongs fibrinolysis in a purified system and plasma milieu (Howes et al, 2012), consistent with results of several clinical studies (Schroeder et al, 2010;Hess et al, 2012;Howes et al, 2012).…”
mentioning
confidence: 99%